(untitled) (Research, Society and Development, 2021)
Giant osteoma appears as a benign nonodontogenic tumor of craniofacial and jaw bones with potential growth. This type of tumor affects different maxillofacial regions, thus requiring proper planning to resolve the patient’s esthetic and/or functional complaints. Medial impairment of the mandible can compromise upper airway (UA) dimensions, leading to respiratory disorders. However, to date, there is a lack of information in the literature about 3D UA imaging protocols for surgical planning. Accurate evaluation, elucidating the involvement of the upper airway patency, may demonstrate the need and urgency for surgical intervention. Therefore, our study aim report a case of a giant mandibular osteoma, associated with a sudden constriction of the oropharyngeal space that was assessed by a Computer Software. The UA was assessed all dimensions, and determining the surgical procedure. In follow up could observed an improvement of UA and patient complain. This study emphasizes the importance of the detailed preoperative assessment of giant osteoma to determinate the correct approach.